Synthesis of aminoquinazoline derivatives and their antiproliferative activities against melanoma cell line - Lee, Junsang; Nam, Bong Soo; Kim, Hwan; Oh, Chang-Hyun; Lee, So Ha; Cho, Seung Joo; Sim, Tae Bo; Hah, Jung-Mi; Kim, Dong Jin; Tae, Jinsung; Yoo, Kyung Ho (Pergamon Press Ltd., 2010)
The synthesis of a novel series of aminoquinazoline derivatives 1a-r and their antiproliferative activities against A375 human melanoma cell line were described. Among them, six compounds showed superior antiproliferative activities to Sorafenib as a reference compound. In particular, the representative compound 1q bearing chromen-4-one moiety exhibited excellent antiproliferative activity (IC50 = 0.006 mu M) and good selectivity over HS27 fibroblast cell line. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: RANDOMIZED PHASE-III; METASTATIC MELANOMA; MALIGNANT-MELANOMA; DACARBAZINE; CHEMOTHERAPY; CISPLATIN; INTERLEUKIN-2; FOTEMUSTINE; EXPERIENCE; THERAPY